Good practices and hindrances to integrate Lean Six Sigma with Industry 4.0 in the chemical sector - Santos Neto, Sergio Tenorio dos [UNESP]; Espuny, Maximilian [UNESP]; Domingues, Pedro; Oliveira, Otávio José de [UNESP] (My University, 2022)
Purpose - This paper identifies and systematized the good practices and hindrances for integrating Lean Six Sigma (LSS) and Industry 4.0 (I4) in a large and important Brazilian chemical company. Design/methodology/approach - The research method used was a single case study in one of the biggest companies of the world chemical sector, recognized for innovating and constantly investing in its processes. Findings – This paper identifies good practices and difficulties for integrating LSS and I4, considering the synergistic and dissonant aspects between the themes. Practical implications - In an applied way this work allows managers to have access to knowledge capable of helping their companies to become leaner, agile, flexible, and digital, generating an important advantage over the competition. Originality/value - In general terms, the systematization carried out in this work adds to the state of the art, important and unprecedented knowledge about good practices and difficulties between LSS and I4 in the chemical sector.
Keywords: Good Practices; Industry 4.0; Integration; Lean Six Sigma